Nature exposure and positive body image: (Re-)examining the mediating roles of connectedness to nature and trait mindfulness. (September 2020) - Swami, Viren; Barron, David; Todd, Jennifer; Horne, George; Furnham, Adrian
Highlights: Greater nature exposure was significantly associated with higher body appreciation. Connectedness to nature (CtN) mediated the direct association. Evidence of a serial mediation, first with mindful awareness and second by CtN, was also obtained. Abstract: Previous studies have reported a significant association between nature exposure and positive body image, but understandings of the mechanisms that help to explain this link remain nascent. Here, we considered the extent to which trait mindfulness and connectedness to nature, respectively, mediate the aforementioned relationship both in parallel and serially. An online sample of 398 participants (199 women, 196 men, 3 other; age M  = 28.1 years) from the United Kingdom completed measures of self-reported nature exposure, mindful awareness and acceptance, connectedness to nature, and body appreciation. Results indicated that inter-correlations between scores on all measures were significant and positive. Following the elimination of non-significant pathways, path analysis resulted in an adequately-fitting model in which the direct relationship between nature exposure and body appreciation was significant. In addition, connectedness to nature – but not trait mindfulness – significantly mediated the direct relationship. Finally, we also found evidence of a serial mediation, where the association between nature exposure and body appreciation was mediated by mindful awareness followed by connectedness to nature. The implications of these results for scholarly and practitioner understanding of the impact of nature exposure on positive body image are discussed in conclusion.